WORKING RELATION BETWEEN HEAD OF THE VILLAGE AND CONSULTATIVE BODY OF THE VILLAGE (BPD) ACCORDING TO LAW NUMBER 6 OF 2014 CONCERNING VILLAGE - Anwar, Khaeril (Jurnal IUS, 2015)
The existence of Law Number 6 of 2014 concerning Village is expected to be able to accommodate the interest and needs of the Villagers. Governance of the Village is organized by Head of the Village and the consultative body of the Village (BPD). The head of the Village is in charge to organize the governance of the Village, implement the development of the Village, maintenance the Villageâs societal matter and empowering the Villagers. Whereas BPD is functioned to discuss and agrees on draft of Village regulation together with the Head of the Village, accommodate and distribute aspiration of the Villagers and supervising performance of the Head of the Village. According to research result, the establishment of Law Number 6 of 2014, there are amendments on position, duties, function and authority of the Head of the Village and BPD, where the Head no longer responsible to BPD. Working relation between Head of the Village and BPD in partnership, consultation and coordination which regulated in Article 1 section 7, stated that Head of the Village and BPD shall discuss and agrees regulation of the Village, Article 11 section 1 regulates that Head of the Village and BPD may initiate status amendment of Village to be urban Village (Kelurahan) through Village deliberation. Article 27 letter c contained obligation of the Head of the Village to provide written report on governance organization to BPD, Article 32 section 1 obliged BPD to writtenly inform Head of the Village concerning expiration his service period at least 6 month in advance of the due date. Article 73 section 2, stated that Head of the Village may proposed draft of income and expenses budget of the Village and having consultation with BPD, Article 77 section 3 regulated that Head of the Village and BPD shall jointly consulting the management of assets of the Village.Keywords: Village governance, working relation between Head of the Village and BPD